Criminalizing Civil Law Actions of Default into Criminal Acts of Fraud: A Human Rights Perspective - Yonatan; Wijayanta, Tata; Sugiri, Bambang; Sukarmi; Sulistio, Faizin (Yuridika, 2024)
The terms "Default" and "Fraud" and/or “Embezzlement” are often interchanged without clarity of meaning in many discussion forums, both oral and written. This confusion can be seen from the many court decisions that acquit defendants from prosecution which have permanent legal force. The public often hears that law enforcers carry out criminalization, such as witnesses becoming suspects, suspects becoming defendants and so on by shifting the civil legal action of Default to criminal act of Fraud and/or Embezzlement. Using 'criminalization' and 'criminalized' in this article is considered inappropriate, so it has been replaced by 'criminalizing' and 'criminalized'. If there is an action to shift the civil legal act of Default into a criminal act of Fraud and/ or Embezzlement, so from a human rights perspective, it is against the law. By using normative legal research methods, this paper examines how to differentiate civil legal acts of Default from criminal acts of Fraud and/or Embezzlement, how to apply civil compensation in cases where there are already criminal legal remedies, and what is the legal and human rights perspective when criminalization occurs. This paper uses a statutory approach and a case approach. The results show: First, there is a real difference between civil legal acts of Default and criminal acts of Fraud and/ or Embezzlement; Second, the application of compensation can be carried out through criminal and civil procedural law mechanisms; Finally, criminalizing civil legal acts into criminal acts is a form of violation of human rights.